1996
DOI: 10.1007/s002940050152
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a cDNA encoding enolase from the filamentous fungus, Aspergillus oryzae

Abstract: A 1.6-kbp full-length cDNA for the Aspergillus oryzae enolase gene (enoA) was cloned. The sequenced insert contained a continuous open reading frame of 1314 bp encoding a protein of molecular weight 47 405. Among all enolases sequenced to-date, the deduced amino-acid sequence showed the highest homology (74.9%) with Candida albicans enolase (ENO1). Strong codon biases and multiple transcription start sites downstream from CT-blocks in the 5'-flanking region suggested strong expression. enoA mRNA was found to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…2. The probe for the enolase (enoA) gene (Machida et al 1996) was used as a loading control as its transcript levels are equal during cultivation on different carbon sources (Nakajima et al 2000). The glaB gene was transcribed to a very low level at 17 h in 2% WLM (lane 1) compared to that on 2% WSM (lanes 5-8).…”
Section: Resultsmentioning
confidence: 99%
“…2. The probe for the enolase (enoA) gene (Machida et al 1996) was used as a loading control as its transcript levels are equal during cultivation on different carbon sources (Nakajima et al 2000). The glaB gene was transcribed to a very low level at 17 h in 2% WLM (lane 1) compared to that on 2% WSM (lanes 5-8).…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids from three independent clones were isolated, and the sequence from each of these was compared with the VRG4 gene isolated by PCR from the isogenic parental strain and cloned in the same way to exclude PCR-derived mutations. DNA sequencing was performed as described (22) using the Thermo Sequenase cycle sequencing kit (Amersham Pharmacia Biotech), using an automated LI-COR 4000L DNA sequencer.…”
Section: Methodsmentioning
confidence: 99%
“…We have established that this gene encodes enolase and that the acuN356 mutation results from a translocation breakpoint in the 59 region separating glycolytic from gluconeogenic regulation, leading to loss of the ability to use gluconeogenic carbon sources while growth is unaffected on glycolytic carbon sources. Analysis of the 59 region of the enolase gene from A. oryzae showed transcription start points at À17, À38, and À45, and deletion analysis of the promoter indicated that a 100-bp sequence between À121 and À228 is necessary for expression on glucose (Machida et al 1996;Figure 6.-Effects of the acuK248 and acuM301 mutations on gene expression. (A) Effects on AcuF-LacZ expression.…”
Section: Discussionmentioning
confidence: 99%